The Influence of Workload and Work Life Balance on Employee Performance through Job Burnout on Swarga Suites Bali Berawa - Wibisono, Gunawan; Nugraha, Surya; Negara, Made Dwipa (Akademi Komunitas MAPINDO, 2024)
Management of human resources in an organization is an important aspect, because HR will have a positiveimpact on organizational development. This study aims to determine and analyze the effect of workload andwork life balance on employee performance through job burnout. This research was conducted at the Biro SDMPolda Bali. The population in this study were all employees of the Bali Police HR Bureau with a total of 88employees. The sample used is the census method so that the entire population is used as a sample. Collectingdata using questionnaires. The data analysis technique used is SEM-PLS. The results of this study indicate thatworkload has a negative and significant effect on employee performance. Work life balance has a positive effecton employee performance. Job burnout has a negative and significant effect on employee performance.Workload has a positive and significant effect on job burnout. Work life balance has a negative and significanteffect on job burnout. Job burnout is able to mediate the effect of workload on employee performance. Jobburnout is able to mediate the effect of work life balance on employee performance.Keywords: Workload, Work Life Balance, Employee Performance, Job Burnout